Kawasaki Disease: A Clinician’s Update - Nathan Jamieson; Davinder Singh-Grewal (International Journal of Pediatrics)
Aims. Kawasaki disease is an acute systemic vasculitis and is the most common cause of acquired heart disease in children in the developed world. This review aims to synthesise recent insights into the disease and provide an update for clinicians on diagnostic and treatment practices. Methods. We conducted a review of the literature exploring epidemiology, aetiology, diagnosis, and management of Kawasaki disease. We searched MEDLINE, Medline In-Process, Embase, Google Scholar, and reference lists of relevant articles. Conclusions. Kawasaki disease is a febrile vasculitis which progresses to coronary artery abnormalities in 25% of untreated patients. The disease is believed to result from a genetically susceptible individual’s exposure to an environmental trigger. Incidence is rising worldwide, and varies widely across countries and within different ethnic groups. Diagnosis is based on the presence of fever in addition to four out of five other clinical criteria, but it is complicated by the quarter of the Kawasaki disease patients with “incomplete” presentation. Treatment with intravenous immunoglobulin within ten days of fever onset improves clinical outcomes and reduces the incidence of coronary artery dilation to less than 5%. Given its severe morbidity and potential mortality, Kawasaki disease should be considered as a potential diagnosis in cases of prolonged paediatric fever.